Contrastive analysis of some Spanish and English verbal patterns in order to predict difficulties for Filipino college students learning Spanish - Antonio, Antolina T. 1919- (1967)
This study aims to: (1) provide a descriptive-contrastive analysis of verbal patterns in Spanish and English, (2) predict some learning difficulties for Filipino college students on the basis of the descriptive-analysis thus provided, and (3) provide a theoretical scale of learning difficulties that will serve as basis for future research on the same difficulties or other learning problems in the study of Spanish among Filipino college students. The result of this contrastive analysis may be used as a guide for teachers, supervisors and writers of instructional materials for basic Spanish courses intended for Filipino college students or for English speakers learning Spanish.
Thesis (M.A.)--University of the Philippines, Diliman.
Keywords: Spanish language -- Verb; English language -- Verb